Cost-effective device for locating and circumscribing superficial tumors with contrast enhancement and fluorescence quantification - A.M. Udeneev; N.A. Kalyagina; K.T. Efendiev; A.A. Febenchukova; A.M. Kulichenko; A.A. Shiryaev; T.N. Pisareva; K.G. Linkov; M.V. Loshchenov (Photodiagnosis and Photodynamic Therapy, 2024)
Background: Two Bispectral contrast enhancement approaches for the fluorescence diagnosis with chlorine-e6 and a wide field-of-view imaging system with fluorescence excitation at 405 nm and time-resolved background suppression were analyzed and compared. Methods: Two techniques for the contrast enhancement of a fluorescent video system (Red/Green (R/G) ratio and Red-Green (R-G)) with time-resolved background suppression for fluorescent diagnosis (FD) were tested in four patients with basal cell carcinoma (BCC). Results: The results of both contrast enhancement methods were compared for the diagnostic efficiency for FD of BCC. Both techniques successfully determined the boundaries of the lesions and the fluorescence intensity. Conclusions: Both contrast enhancement modes have proven effective in identifying tumor borders in cases of low contrast in BCC FD with Ce6. While the Red/Green (R/G) mode provides sharper lesion borders, the Red minus Green (R-G) mode visualizes more fluorescent features and makes it easier to assess the lesion margins.